Work-Life Balance and Job Satisfaction Towards Employee Performance at The Center for Development of Quality Assurance of Vocational Education (BBPPMPV) In Business and Tourism - Hidayatulloh, Syafrudin; Ariyanti, Eti (STEBIS Bina Mandiri, 2025)
The purpose of this study is to determine the effect of work-life balance and job satisfaction on the performance of employees of the Center for the Development of Vocational Education Quality Assurance (BBPPMPV) Business and Tourism both partially and simultaneously. The research method used is a quantitative method with a descriptive approach. The sampling technique used is saturated sampling technique, namely using a sample of 73 respondents from the entire population. Data analysis techniques used are instrument testing, classical assumption testing, linear regression analysis, coefficient of determination analysis, hypothesis testing. This is evidenced by the results of the work-life balance hypothesis test obtained a t-value of 8.082> t-table 1.993 and is strengthened by the ρ value <Sig.0.05 or significance value <0.05 (0.000<0.05) job satisfaction obtained a t-value of 8.109> t-table 1.993 and is strengthened by the ρ value <Sig.0.05 or significance value <0.05 (0.000>0.05). The results of the study show that work-life balance and job satisfaction simultaneously have a positive and significant effect on employee performance at the Center for the Development of Vocational Education Quality Assurance (BBPPMPV) for Business and Tourism, as shown by the multiple linear regression equation Y = 7.984 + 0.386X1 + 0.436X2. This is evidenced by the results of the simultaneous hypothesis test, which obtained the F-value (64.666>F-table 3.13) and is strengthened by a significance value <0.00 (0.000 <0.05). The results of the coefficient of determination test for the work-life balance and job satisfaction variables have an influence of 63.9% on employee performance at the Center for the Development of Vocational Education Quality Assurance (BBPPMPV) for Business and Tourism. Thus, H03 is rejected and Ha3 is accepted. This means that there is a significant simultaneous influence between work-life balance (X1) and job satisfaction (X2) on employee performance (Y).